(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides a socio-philosophical analysis of the concept of “civilization”, scientific definitions, identification of important aspects of the scientific definitions attached to it, methodological relevance, concepts related to civilization, forming approaches to understanding the nature of social phenomena, a new scientific paradigm, a variety of civilizational approaches, aims to study the static and dynamic state of society both vertically and horizontally, and compare them with each other.